2013
DOI: 10.1007/s00464-013-3151-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection of gastrointestinal lipomas: a single-center experience

Abstract: Endoscopic treatment appears to be a safe and effective treatment for GI lipomas, including large lipomas (≥2 cm in diameter).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
89
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 21 publications
0
89
0
1
Order By: Relevance
“…ERs are reported to be useful in the treatment of various benign and malignant duodenal lesions, including intramucosal adenocarcinomas, adenomas, lipomas and neuroendocrine tumors (20,(36)(37)(38)(39). The required specific technique (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…ERs are reported to be useful in the treatment of various benign and malignant duodenal lesions, including intramucosal adenocarcinomas, adenomas, lipomas and neuroendocrine tumors (20,(36)(37)(38)(39). The required specific technique (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The mucosa regenerated on the unroofed surface after 1 month in the 1st patient, whereas endoscopic findings showed that adipose tissue had not drained in the 2nd patient within 1 month, and additional endoscopic mucosal resection (EMR) was required. Unroofing resulting in incomplete resection that requires additional EMR has been reported [9]. More investigation is needed about lipomas treated by endoscopic unroofing, particularly those from which adipose tissue does not drain.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristically, the ‘pillow sign’ is an endoscopic feature which refers to the indentation of colonic lipomas with biopsy forceps, aiding a clinical diagnosis . Colonoscopy can be therapeutic with descriptions of complete and partial resections previously published …”
mentioning
confidence: 99%
“…Direct endoscopic visualization allows for assessment of base broadness, size and degree of obstruction, and allows for biopsies to confirm the diagnosis and exclude malignancy. [5][6][7] Characteristically, the 'pillow sign' is an endoscopic feature which refers to the indentation of colonic lipomas with biopsy forceps, aiding a clinical diagnosis. 8 Colonoscopy can be therapeutic with descriptions of complete and partial resections previously published.…”
mentioning
confidence: 99%
See 1 more Smart Citation